Persebaran Intrusi Air Laut Pada Air Tanah Di Pulau Madura - zafira mauluida; Novirina Hendrasarie (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
On Madura Island, many people use groundwater by drilling wells for their daily needs. The groundwater problem is related to the non-compliance with the quality standards for clean and potable water according to the Regulation of the Minister of Health of Indonesia No. 492 of 2010. The aim of this study is to determine the extent of seawater intrusion in Madura. The parameters tested in the laboratory are in accordance with the Minister of Health Regulation of Indonesia number 416 of 1990, which regulates the standards and monitoring of water quality, namely total hardness and TDS. The salinity value is also measured as a determination in the classification of groundwater salinity to determine the influence of seawater intrusion. From these results, it can be known that the groundwater in Krampo Hamlet, Bankalan Regency (A2) and Padelegan Village, Pamekasan Regency (C1) have the highest salinity, hardness and TDS values in each zone. Krampo Hamlet (A2) has a salinity value of 1.095%, hardness 605 mg/l, TDS 1290 mg/l while Padelegan Village (C1) has a salinity value of 1.4%, hardness 510 mg/l and TDS 1440 mg/l. At 8.5 km from the seawater intrusion in Krampo Hamlet, Bangkalan Regency (A2) and 9 km in Padelegan Village, Pamekasan Regency (C1). An alternative solution that can be tried is to plant mangroves using a spacing system.